Lexicalization of Light Verb Structures and the Semantics of Nouns - M. Teresa Espinal (Universitat Autònoma de Barcelona, 2004)
In this study I shall focus on two Romance idiomatic patterns and the semantics of nouns. It is shown that idioms, in addition to having distinct basic argument structure representations, are formed in syntax by various instantiations of Merge. It is argued that there is a lexicalization pattern reflecting semantic conflation (Talmy 1985, 2000) between cause and degree. This pattern, in syntactic terms, is the output of subsequent Merge operations (Chomsky 1995) between the object noun of a monadic argument structure, an indefinite quantifier and an adjunct phrase. The study of this lexicalization pattern is of interest with regard to the semantics of bare nouns, especially of bare count singular nouns in object position; it is proved that bare nouns are interpreted as properties, and, because of this, they permit quantification over degrees. By contrast, there is a second lexicalization pattern starting from a composite argument structure which licenses an individual or a kind denoting reading for the DP object.